Enrichment of fruit wastes with white rot fungi under submerged state bioconversion - Jamal, Parveen; Saheed, Olorunnisola Kola; Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Abdul Karim, Mohamed Ismail (2013)
In order to measure the suitability of microbes and substrate composite for animal feed supplements, submerged state bioconversion (SmB) was carried out. Selected microbes Phanerochaete chrysosporium (P. chrysosporium), Panus tigrinus (M6) and RO2 were grown solely on the liquid and solid substrates and their composite. On banana peel (solid and liquid), RO2 produced the highest protein (15.88 and 14.08 mg/g) as compared to P. chrysosporium (15.09 and 13.56 mg/g) and M6 (13.24 and 8.07 mg/g). For pineapple peel (solid and liquid), RO2 protein was 17.71 and 12.79 mg/g, which was higher than M6 protein (12.61 and 12.32 mg/g) and P. chrysosporium protein (12.27 and 6.85 mg/g). On composite substrate (solid and liquid); Banana, Pineapple and Papaya (BPinPw) P. chrysosporium gave 18.59 and 13.48 mg/g protein. On Banana and Pineapple (BPin) the protein content were recorded as18.05 and 15.75 mg/g, which was higher than Papaya and Pineapple (PinPw) and Banana and Papaya (BPw)composite. M6 has 15.4 and 9.78 mg/g on BPinPw, 13.84 and 13.59 mg/g on BPw, 20.82, and 22.97 mg/g on BPin and 18.29 and 11.59 mg/g on PinPw. RO2 produced 19.91 and 19.66 mg/g on BPinPw, 14.80 and 11.80 mg/g on BPw. 26.34 and 17.91 mg/g BPin and 20.91 and 18.38 mg/g on PinPw.